Pengaruh Hukuman dan Hadiah Terhadap Hasil Belajar Matematika Kelas IV SDN 02 Bumiharjo Keling Jepara - Hidayatullah, M. Lutfi; Wiranti, Wiranti (Jurnal Riset Madrasah Ibtidaiyah, 2024)
The aim of this research is to see whether reward and punishment have an influence on students' mathematics learning outcomes. This research uses quantitative methodology with ex post facto techniques. The subjects or population of the research carried out in class IV of SDN 02 Bumiharjo consisted of twenty students. There are two variables in this research, namely the independent variable and the dependent variable. Reward and punishment are the independent variables in this research, while students' mathematics learning outcomes are the dependent variable. This research uses questionnaires and documentation to collect data, and the SPSS 23.0 application is used to carry out validity, reliability, prerequisite tests and F tests on the data. The F test results show a significance value of <0.05 or 0.033<0.05 with an R value of 0.478. This shows that reward and punishment influence students' mathematics learning outcomes. Thus, it can be concluded that reward and punishment have an influence of 47.8 percent, while the rest is influenced by other factors.